2015
DOI: 10.1002/ajim.22522
|View full text |Cite
|
Sign up to set email alerts
|

Work organization, exposure to workplace hazards and sickness presenteeism in the European employed population

Abstract: Our results support the importance of work-related factors, especially psychosocial exposures and organizational features, in determining workers' SP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
22
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 48 publications
(112 reference statements)
6
22
1
1
Order By: Relevance
“…Presenteeism is summarily defined as working ill instead of having taken leave (4) and entails lower performance at work due to health problems (3,5,6). Absenteeism is defined as absence from work (7) due to valid (sick-leave) or less valid reasons (taking a day-off) (8).…”
Section: Abstract: Nurses; Physicians; Work Performancementioning
confidence: 99%
See 3 more Smart Citations
“…Presenteeism is summarily defined as working ill instead of having taken leave (4) and entails lower performance at work due to health problems (3,5,6). Absenteeism is defined as absence from work (7) due to valid (sick-leave) or less valid reasons (taking a day-off) (8).…”
Section: Abstract: Nurses; Physicians; Work Performancementioning
confidence: 99%
“…Two longitudinal studies have indicated that presenteeism may increase the risk of future health disorders (15,16), as it stands in the way of recovery (3,17). In fact, presenteeism can lead to more sickness absence, as indicated by the positive correlation between the two in several studies (4,18,19).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Sickness presenteeism (SP) is a phenomenon in people who attend work despite being sick or feeling like they should have taken sick leave (Aronsson, Gustafsson, & Dallner, ). This definition is primarily used in European research, and research in the United States of America defines SP as reduced work performance due to the presence of health problems (d'Errico, Ardito, & Leombruni, ; Lerner, Amick, Malspeis, & Rogers, ; Schultz & Edington, ). Employees who come to work sick generally feel sick and tired and have a low work morale and a low opinion of their work, which results in low work productivity and poor work quality (Ashby & Mahdon, ; Goetzel et al, ; Koopman et al, ; Middaugh, ; Miraglia & Johns, ).…”
Section: Introductionmentioning
confidence: 99%